Domestic factors and strategic partnership: Redefining Philippines-Japan relations in the 21st century - Trinidad, Dennis D. (Animo Repository, 2017)
The Joint Statements and declarations on the establishment, promotion, and strengthening of strategic partnership by the leaders of Japan and the Philippines since 2011 indicate an ardent desire toward making security and defense cooperation a salient feature of their 21st century bilateral relationship. Scholars would point to the “China factor” as a convenient reason to explain the strategic trajectory of this evolving relationship. While this study does not discount the “China factor” as a motivating force behind this change, it asserts that both nations were able to extend their partnership into the security realm because of some enabling domestic factors. Nonetheless, a Duterte Presidency may seriously derail this effort. © 2017 Policy Studies Organization. Published by Wiley Periodicals, Inc.